2017
DOI: 10.1111/jfpp.13555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of location and Citrus species on total phenolic, antioxidant, and radical scavenging activities of some Citrus seed and oils

Abstract: The objective of this study was to determine the total phenolic content, antioxidant activity, and radical scavenging effect of the seeds and seed oils of some Citrus fruits (mandarin, orange, and lemon) collected from different locations of Turkey on November in 2008 and 2009. The total phenolic content, antioxidant activity, and radical scavenging of citrus are 209.90-287.20 mg gallic acid equivalent (GAE)/kg, 1.24-2.04 mmol TE/kg, and 2.21-0.73 DPPH. IC 50 of mandarin;198.40-230.40 mg GAE/kg, 1.49-1.83 mmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…The antioxidant capacity of the nutraceutical product was similar to those found in mandarin, orange, grapefruit and lemon, among other citrus fruits . These results indicated that the powdered product, despite being exposed to changes in its structure, still has similar values to different fresh products . Although it is true that the main advantage of the method established for the quantification of antioxidant activity is its simplicity, the biggest disadvantage is that the results can be influenced by many factors, such as the interaction of the antioxidants in the sample, reagents, pH, times or free radical production .…”
Section: Resultssupporting
confidence: 55%
“…The antioxidant capacity of the nutraceutical product was similar to those found in mandarin, orange, grapefruit and lemon, among other citrus fruits . These results indicated that the powdered product, despite being exposed to changes in its structure, still has similar values to different fresh products . Although it is true that the main advantage of the method established for the quantification of antioxidant activity is its simplicity, the biggest disadvantage is that the results can be influenced by many factors, such as the interaction of the antioxidants in the sample, reagents, pH, times or free radical production .…”
Section: Resultssupporting
confidence: 55%
“…In the DPPH test, the stable free radical with dark violet color interact with the phenolic compounds and immediately after receiving proton from them, it instantly loses its chromophore and becomes yellow (Farahmandfar et al, 2018;İnan, Özcan, & Aljuhaimi, 2018). In the DPPH test, the stable free radical with dark violet color interact with the phenolic compounds and immediately after receiving proton from them, it instantly loses its chromophore and becomes yellow (Farahmandfar et al, 2018;İnan, Özcan, & Aljuhaimi, 2018).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Lower levels of TP were reported by Yilmaz and Güneşer in cold pressed (4.92 mg GA/100 g) and solvent extracted (3.86 mg GA/100 g) lemon seed oils. TPC values in the range 71.12–87.00, 46.63–92.80, and 63.41–92.51 mg GAE/kg of seeds were reported by İnan et al for mandarin, orange, and lemon seed oils, respectively. Otherwise, the TPC average value of 4.43 g kg −1 oil was reported by Jorge et al for orange seed oil obtained by pressing in vegetable oil extractor.…”
Section: Resultsmentioning
confidence: 77%
“…The seeds of Citrus fruits are an interesting source of phenolic compounds, which include phenolic acids, tocopherols, flavonoids and tannins . Also Citrus seed oils have been reported to possess significant levels of phenolic compounds . TPC values of 1.20, 1.01, 1.15 mg GAE/g of oils were previously determined by using the Folin–Ciocalteu reagent, for lemon, tangerine ( C. reticulata Blanco) and orange ( C. sinensis L. Osbeck) seeds, respectively .…”
Section: Resultsmentioning
confidence: 99%